TRANSPARENCY AND ACCOUNTABILITY IN THE MANAGEMENT OF HAJJ FUNDS BY BPKH: A LITERATURE REVIEW - Loso Judijanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the implementation of the principles of transparency and accountability in the management of Hajj funds by the Hajj Financial Management Agency (BPKH) based on a literature review. Hajj fund management in Indonesia is regulated in Law No. 34/2014 which requires BPKH to manage Hajj finances in an open, accountable, and accountable manner to the public, especially prospective pilgrims as fund owners. This study uses descriptive-analytic method with data obtained from various literature sources, financial reports, and related regulations. The results of the study show that BPKH has implemented various transparency mechanisms, such as periodic financial reporting, external audits by the Supreme Audit Agency (BPK), as well as the utilisation of information technology through virtual account services and the Integrated Hajj Financial System (Siskehat) that allows pilgrims to monitor the balance and value of their fund benefits directly. The level of disclosure of Hajj financial management information by BPKH is considered high and in line with good governance standards, although there are still challenges in delivering information on the value of benefits proportionally and in real time to all prospective pilgrims. Overall, the management of Hajj funds by BPKH has fulfilled the principles of transparency and accountability as mandated by the regulation, marked by an Unqualified Opinion (WTP) from BPK and an increase in the value of Hajj fund benefits every year. However, strengthening socialisation, supervision, and the development of more varied Islamic investment instruments are still needed so that public trust in the management of Hajj funds can continue to increase and the benefits are more optimal for pilgrims and the benefit of Muslims in Indonesia.